Development of integrated science textbooks by applying the enrich tool - Zain, Saidi; Ahmad, Zuraida; Ismail, Ahmad Faris; Salah, Machouche; Mohamad, Souad A. (Journal of Education and Social Sciences (JESOC), 2016)
The Islamization of Human Knowledge (IoHK) focuses primarily on the integration between the curriculum for professional courses and the Islamic perspective, in addition to the training of educators to be murabbis, and the infusion of teaching materials with Islamic outlook and Islamic perspectives. The availability of teaching materials which are infused with the Islamic perspective are still lacking, especially for science based subjects. Therefore, a study on the development of an Islamically integrated Physics Text book for the matriculation level was conducted. As a result, this paper is produced to report on the appropriateness of the proposed tool used for this purpose. The ENRICH tool is developed with the expectation that it will give an effective guideline in the Islamization process of any sciences textbook. ENRICH consists of six main processes namely Eliminate (E), Nourish (N), Readapt (R), Infuse (I), Create (C) and Harmonize (H). In the aforementioned case study, the ENRICH tool was applied as a guideline to develop Chapter 3: The Laws of Motion of Physics Textbook, Volume I used at the Centre for Foundation Studies, IIUM as a template. Although there are still plenty of rooms for improvement, it is believed that the Islamized of textbook will aspire students to gain knowledge in Islamic perspective.